Metaphors to work by: the meaning of personal assistance in England. (1st June 2018) - Shakespeare, Tom; Stöckl, Andrea; Porter, Tom
Abstract : Personal assistance is an innovative role within social care whereby disabled people directly employ others to provide support. Defining personal assistance as a commodified support relationship is insufficient as it fails to capture the lived complexity of these relationships. This article reports on qualitative interviews in England with 30 disabled people and 30 personal assistants. In the absence of any normative interpretive framework, participants defined their relationships through metaphor: 'paid friends', 'staff' and 'quasi-family'. We explore the structure and significance of these descriptors, and offer an overview of the emotional, social and cultural dynamics that shape personal assistance relationships, and give them meaning.